The Effectiveness Of Group Learning In Improving Students’Arabic Speaking proficiency - Yusri, Siti Alfathia; Muhammad Samin, Saproni (Perspektif Pendidikan dan Keguruan, 2024)
This research aims to determine the effectiveness of group learning in improving Arabic speaking skills of students at the Arabic Language Education Department, Riau Islamic University. The type of research used in this research is quantitative research with an experimental design. The research instrument used was a test. The techniques used to analyze the data are validity testing, normality testing and hypothesis testing. The population of this study was 150 people and the sampling technique used in this research was random sampling, namely with one group containing eight people. In this study, the researcher used the one-group method where the group contained 8 students and the results of hypothesis testing showed that Sig. (2-Tailed) 0.950 is greater than 0.05 (1/2 value). The conclusion of this study shows that Ho is acceptable. Thus, it can be interpreted that the results of group study among students of the Arabic Language Education Department at Riau Islamic University in improving their Arabic speaking skills are considered effective